Combining ability and heterosis in common bean cultivars - Gonçalves-Vidigal, Maria Celeste; Silvério, Lucas; Elias, Haroldo Tavares; Filho, Pedro Soares Vidigal; Kvitschal, Marcus Vinícius; Retuci, Vanessa Silva; Silva, Claudete Rosa da (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to determine the combining ability and heterosis, for productivity and yield components, in diallel hybrids derived from crossings between BRSMG‑Talismã, IPR Uirapuru, FT Soberano, BRS Campeiro, IAC Tybatã, and IPR Juriti parent cultivars. Fifteen hybrids were generated from diallel crosses, excluding reciprocals. The general and specific combining abilities were significant for plant height, number of pods per plant, number of seeds per plant, number of seeds per pod, 50‑seed weight, and grain yield, indicating the occurrence of both additive and nonadditive genetic effects. The best strategy to be adopted is the use of BRS Campeiro, FT Soberano and BRSMG‑Talismã cultivars in common bean breeding programs involving selection. The most promising combinations were 'IPR Uirapuru' x 'IAC Tybatã', 'IPR Uirapuru' x 'FT Soberano', 'BRS Campeiro' x 'IPR Juriti', and 'BRS Campeiro' x 'IAC Tybatã'. The parentsof these hybrids presented high estimates of specific combining abilities. Hybridization of cultivars belongingto distinguished commercial groups propitiates higher heterosis values in the segregant population.